Inquinamento da particolato a Mottola e aspetti educativi - Potenz, Domenico; Pansini, Gabriella; Ritelli, Lorenza; Trisolini, Raffaella; Acquaro, Vita Maria; Colafemmina, Giuseppe; Carriero, Giorgia (Chimica nella Scuola, 2024)
1The aim of the work is the assessment of particulate air pollution in Mottola in 2022 and the treatment of socio-educational aspects. Measurements of PM 2,5 and PM 10 were made with a laser scattering instrument, both outdoor, in three selected sites, and indoor, in three schools and in three pharmacies. As for the outdoor sites, data analysis shows some high values in the winter period and an annual average of the data collected in the normal limit. The values collected in schools and pharmacies are acceptable, except for one in October, in correspondence to an outdoor peak. Data on Covid-19 infections and bronchodilators used do not correlate with PM 2,5 and PM 10 peaks. Useful suggestions for managing problems caused by particulate matter are given in the conclusions.